Soundtrack Music Videos: The Use of Music Videos as a Tool for Promoting Films (Communication & Society, 2021)
The soundtrack music video is an audiovisual format used by the cultural industries of film and music as a commercial communication tool, since it is based on a song from the soundtrack of a film, so that both the artist that performs the song and the film itself obtain promotional benefits. This paper conceptualizes this poorly studied phenomenon of cross-promotion connecting the music and film industries and uses a content analysis of 119 music videos produced over a period of 33 years in order to study the importance of the artist and the movie in the video, the various strategies developed in order to accomplish its double promotional mission, and the specific formal and strategic features of this audiovisual format. Analysis reveals that the soundtrack music video has the distinctive feature of including promotional elements both for the musical artist and for the movie. Although the artist tends to be more prominent, the vast majority of music videos include images from the film or use various ways of integrating the artist’s identity with the film’s iconography or narrative. Anyway, it is a phenomenon characterized by diversity, with the common pattern of the dual promotional objective, but with different ways of implementing that pattern.